ICT and social change - Cesareo, Giovanni (Javnost (Ljubljana), 2004)
The article identifies contradictions and ambiguities at all levels of the present social changes in order to exploit them and nurture the "culture of choice" we may practice. Ambiguity gives rise to alternative perspectives, which may help us to better understand the social processes in the so called "Information Society" and knowledge industry, avoiding the technological determinism that is so often called forth nowadays. Our research should explore relations between structure and culture, gender, and individual and social groups to highlight differences instead of common values and behaviours, and to enforce the possibility to choose among the different alternatives. Research should also be focused on the subjects able to make thechoice and, finally, practice the change they choose. The article tries to single out the problems that arise among the "autonomous workers" who are constantly increasing their presence in the labour market and the problems that arise among the people who try to use innovatively the "old" and the "new" media
Keywords: družbene spremembe; družbeni procesi; informacijska družba; informacijska tehnologija; information technology; knowledge; znanje